Techno-Prevention in Counterterrorism: Between Countering Crime and Human Rights Protection - Masyhar, Ali; Emovwodo, Silaas Oghenemaro (Lembaga Contrarius Indonesia, 2023)
Terrorism has become a significant concern throughout the world. This concern is supported by the increasing use of the internet, which has triggered an increase in cyberattacks. This research aims to determine the role of governance in counter-cyber terrorism. The normative legal methodology utilized in this study results from an exhaustive literature evaluation. This research shows that the government's role is needed to counter cyber terrorism. Although the Indonesian government has initiated a national cybersecurity strategy and implemented short-term and long-term programs, some obstacles and challenges hinder its implementation. The ITE Law has encouraged Indonesia to establish policies and regulations regarding information security. There have yet to be any regulations regarding cyber-attacks to counter cyber terrorism. Various institutions with common interests in national defense and security, including the cyber domain, must collaborate with BSSN. Other government agencies that depend on each other include the TNI, Polri, Ministry of Defense, BIN, and Ministry of Communication and Information. Apart from that, governance is also needed, including international organizations, several non-governmental organizations (NGOs), government and private governance, and several other components.Â